Improved Electromagnetsim-Like Algorithm for Economic Emission Dispatch Problem - Chooi F.Y.; Chen C.P.; Koh S.P.; Tiong S.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Greenhouse gases; Local search (optimization); Carbon taxes; Economic and emission dispatch; Economic-emission dispatch; Experimental testing; Generation cost; Load demand; Local search; Electric load dispatching